2019
DOI: 10.1002/acn3.50826
|View full text |Cite
|
Sign up to set email alerts
|

Vanishing white matter: deregulated integrated stress response as therapy target

Abstract: Objective Vanishing white matter (VWM) is a fatal, stress‐sensitive leukodystrophy that mainly affects children and is currently without treatment. VWM is caused by recessive mutations in eukaryotic initiation factor 2B (eIF2B) that is crucial for initiation of mRNA translation and its regulation during the integrated stress response (ISR). Mutations reduce eIF2B activity. VWM pathomechanisms remain unclear. In contrast with the housekeeping function of eIF2B, astrocytes are selectively affected in VWM. One st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
136
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(166 citation statements)
references
References 44 publications
(67 reference statements)
17
136
1
Order By: Relevance
“…VWMD astrocytes exhibited increased GADD34 (Fig. 1E), consistent with glia in animal model studies (15) and the hypophosphorylation of eIF2 observed in white matter patient tissue (22).…”
Section: Vwmd Patient Broblasts and Astrocytes Exhibit Dysregulated Isupporting
confidence: 77%
“…VWMD astrocytes exhibited increased GADD34 (Fig. 1E), consistent with glia in animal model studies (15) and the hypophosphorylation of eIF2 observed in white matter patient tissue (22).…”
Section: Vwmd Patient Broblasts and Astrocytes Exhibit Dysregulated Isupporting
confidence: 77%
“…MG132-stressed VWMD astrocytes also showed reduced upregulation of eIF2α phosphorylation and increased CHOP, compared to controls (Figure 1D-F). VWMD astrocytes exhibited increased GADD34 ( Figure 1E), consistent with glia in animal model studies (15) and the hypophosphorylation of eIF2 observed in white matter patient tissue (22).…”
Section: Vwmd Patient Broblasts and Astrocytes Exhibit Dysregulated Isupporting
confidence: 75%
“…ISRIB is thought to allow eIF2B to escape inhibitory complex formation with p-eIF2α, thus limiting repression of protein synthesis while under ER stress (15,24). Treatment of EIF2B5 VWMD mice with ISRIB, or a derivative, 2BAct, ameliorated myelin loss, and improved ISR signature and motor function (15,22,24). It is also worth noting that the stabilising effect of ISRIB may be dependent on the precise mutations and the cellular concentration of p-eIF2α, whereby it has been found to inhibit low level but not high level ISR activation (22,39).…”
Section: Discussionmentioning
confidence: 99%
“…However, in some circumstances its heightened activity is associated with unfavourable outcomes, motivating a search for ISR inhibitors. When applied to cells or administered to animals, the druglike small molecule, ISRIB, disrupts the ISR (Sidrauski et al, 2013), and has been reported to exert beneficial effects in models of neurodegeneration (Halliday et al, 2015;Zhu et al, 2019), head injury (Chou et al, 2017) and dysmyelination (Wong et al, 2018;Abbink et al, 2019).…”
Section: Introductionmentioning
confidence: 99%